Differentiation between Eutypa lata and Cryptovalsa cf ampelina by means of Cellular Fatty Acid Analysis - Ferreira, J. H. S.; Augustyn, 0. P. H. (South African Journal of Enology and Viticulture, 2017)
Eutypa lata is generally accepted to cause dieback in grapevines. Cryptovalsa cf ampelina may possibly contribute to this phenomenon but cannot be distinguished from the former species, due to the identical morphology of the anamorph stages. Cellular fatty acids were recovered from both fungi and analysed by capillary gas chromatography using a polar column. Fatty acids were identified by GC-MS analyses of picolinyl esters. The mean relative percentages of C16:0, C16:1(9) and C18:0 differed significantly (p~0,01) between the species and allowed rapid differentiation. The 16:0/Cl6:1(9) and (C16:1(9)/C18:0 ratios were of similar diagnostic value.